Adubação fosfatada e épocas de cultivo na composição química de sementes de cultivares de feijoeiro - Zucareli, Claudemir (2014)
Phosphorus is a limiting nutrient in common bean grain yield and may influence the chemical composition of seeds. The aim was to assess the effects of phosphorus fertilization and planting dates ('water' and 'dry') in the seeds chemical composition of two dry bean cultivars. A field experiment was carried out in Botucatu (SP) in a randomized block design with five replications. Two dry bean cultivars 'Carioca Precoce' e 'IAC Carioca Tybatã' were evaluated in growing 'water' and 'drought' in six levels of P2O5 (0, 30, 60, 90, 120 and 150kg ha-1) applying superphosphate at planting row. It was assessed seed samples to determine the levels of N, P, K, Ca, Mg, S, Cu, Mn, Fe, Zn, total and reducing sugar and protein. The phosphorus in the soil alters the seeds chemical composition, increasing contents of P and decreasing Ca and Cu contents. The K and Fe contents showed minimum point at a level of 69.9 and 66kg ha-1 of P2O5, respectively. It was observed that occurred increase in contents of N, P, and protein of seeds in the growing season 'drought'. The cultivar 'Carioca Precoce' showed higher N content and protein of seeds than 'IAC Carioca Tybatã'. There is interaction between cultivar and growing season for the content of S, Mn, Fe, Ca, Mg, Cu, total and reducing sugars.